2016
DOI: 10.1080/10447318.2016.1150642
|View full text |Cite
|
Sign up to set email alerts
|

The Stroop and Reverse Stroop Effects as Measured by an Interactive Tabletop

Abstract: International audienceAn interactive tabletop equipped with RFID technology implemented the Stroop and reverse-Stroop tasks. Participants moved a tangible object into one of four displayed virtual zones, which were identified either by a color border or the name of a color written in black. The correct target zone corresponded either to the color (Stroop) or meaning (reverse Stroop) of a word displayed in congruent or incongruent colored LED lights (e.g., “YELLOW” displayed in yellow or red, respectively). Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Likewise, our finding of RSE of 20% is in line with previous studies (11-27%) [18,19]. We did not find a significant increase in the number of errors between CIT color and grey grids.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Likewise, our finding of RSE of 20% is in line with previous studies (11-27%) [18,19]. We did not find a significant increase in the number of errors between CIT color and grey grids.…”
Section: Discussionsupporting
confidence: 82%
“…Previous experiments were also able to show that SE could be almost eliminated by incorporating visually guided actions in color matching in place of verbal responses (Stroop condition, manual response task) [16,17]. Studies examining manual response tasks in the Reverse Stroop condition demonstrated that reaction time increased by 11-27% when compared to the neutral condition [18,19].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation